Patterns of resilience: A scoping review and bibliometric analysis of resilient health care. (October 2019) - Ellis, Louise A.; Churruca, Kate; Clay-Williams, Robyn; Pomare, Chiara; Austin, Elizabeth E.; Long, Janet C.; Grødahl, Anne; Braithwaite, Jeffrey
Graphical abstract: Highlights: The resilient health care field is formalising as a paradigm. Empirical work in resilient health care is limited, but growing. Qualitative studies are important for understanding systems. The Resilience Health Care Net is a key research hub for connectivity. Having a primary journal dedicated to the topic of resilience could be of value to the field. Abstract: Following its emergence from the field of resilience engineering in 2012, resilient health care has grown to underpin a new paradigm of safety that leverages an understanding of what goes right to improve patient care. The aim of this paper was to review the resilient health care literature via multiple analyses, in order to examine growth and global longitudinal trends through bibliometric analysis and the influence of this body of work through citation and network analyses. We searched five academic databases (Scopus, CINAHL, EMBASE, Medline and Safety Science abstracts in ProQuest) using key resilience engineering terms, for literature published from inception to October 2018. The search was augmented with a by-hand examination of the four resilient healthcare books published to date. English-language literature in the context of health care, where system agents were humans, and where resilience was the core focus were included, resulting in a total of 197 publications. While the majority of outputs were found to be non-empirical (58.9%), there has been substantial growth in empirical work in recent years. Journal articles (n = 102) were spread widely across 63 journals. The co-authorship network analysis showed a strong clustering around the founding resilient health care authors. We conclude that that resilient health care is maturing, and formalising into a distinctive paradigm.